Saliva substitutes in combination with high-fluoride gel - Zandim-Barcelos, Daniela Leal [UNESP]; Kielbassa, Andrej M.; Sampaio, Jose Eduardo Cezar [UNESP]; Tschoppe, P. (Springer Nature, 2015)
Objective This study aimed to determine whether the application of a high-fluoride gel could increase the remineralization of subsurface dentin lesions stored in saliva substitutes. Materials and methods Demineralized bovine dentin specimens were stored in mineral water (W), Glandosane (G), or modified Saliva natura (SN). Different treatments were applied twice daily: no treatment, Elmex sensitive mouth rinse (E), ProSchmelz gel (P), Duraphat toothpaste (D), ED, PD, and EPD. Differences in mineral loss were evaluated by transversal microradiography after 2 and 5 weeks. Results The treatments with E, D, and ED inhibited the mineral loss induced by G and enabled some mineral gain. ProSchmelz was not able to inhibit the demineralizing effect of G. This high-fluoride gel induced an erosive mineral loss in combination with G. The use of ProSchmelz in combination or not with other fluoride products did not increase remineralization of specimens stored in SN or W (p>0.05). ProSchmelz resulted in an erosion of the specimens stored in W and revealed a lower mineralized surface layer of specimens stored in SN. Conclusion Topical application of high-fluoride gel reduced the mineral loss induced by G but resulted in an erosion of specimens’ surface. In addition, ProSchmelz did not demonstrate beneficial effects in combination with SN on subsurface dentin lesion remineralization. Clinical relevance Within the limitations of an in vitro study, it was concluded that the application of a high-fluoride gel did not promote additional effects on remineralization of subsurface dentin lesions in combination with saliva substitutes when compared to products with lower fluoride concentration.
Keywords: Hyposalivation; Fluoride; Saliva substitute; Demineralization; Remineralization; Microradiography